TRADISI MEBOROS KIDANG DALAM UPAYA PENINGKATAN SRADHA BHAKTI MASYARAKAT DESA PEDAWA KABUPATEN BULELENG (Perspektif Pendidikan Agama Hindu) - Angga Richa; Ni Rai Vivien Pitriani; Ni Luh Purnamasuari Prapnuwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Meboros Kidang tradition is one of the indigenous cultural practices of the Pedawa community that plays a significant role in the implementation of Hindu religious ceremonies. However, public understanding of the Hindu religious education values embedded in this tradition remains limited, highlighting the need for a comprehensive investigation. This study aimed to analyze the significance, implementation process, and implications of the Meboros Kidang tradition in strengthening the sradha (faith) and bhakti (devotion) of the Pedawa community in Banjar District, Buleleng Regency. A qualitative approach with an ethnographic design was employed. Data were collected through non-participant observation, semi-structured interviews, documentation, and literature review, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the Meboros Kidang tradition constitutes an integral part of the Ngusaba Malunin and Ngrebeg ceremonies, implemented in accordance with customary village regulations (awig-awig). The tradition embodies religious, social, cultural, and ecological values while serving as a medium for transmitting Hindu religious education values across generations. Furthermore, it enhances community sradha and bhakti through the internalization of yadnya values, devotion to Ida Sang Hyang Widhi Wasa, preservation of local culture, reinforcement of mutual cooperation, and environmental stewardship. This study concludes that the Meboros Kidang tradition plays a strategic role in preserving cultural heritage while fostering the religious and social life of the Pedawa community.